Idiopathic Colitis in Rhesus Macaques Is Associated With Dysbiosis, Abundant Enterochromaffin Cells and Altered T-Cell Cytokine Expression. Issue 5 (September 2018) - Laing, Steven T.; Merriam, David; Shock, Barbara C.; Mills, Sarah; Spinner, Abbie; Reader, Rachel; Hartigan-O'Connor, Dennis J.
Idiopathic chronic diarrhea (ICD) is a common ailment affecting captive rhesus macaques ( Macaca mulatta ). ICD cases are characterized by diarrhea in the absence of commonly identified diarrheal pathogens and multiple recurrences even after supportive therapy. Histologically, the disease is characterized by lymphoplasmacytic colitis. We identified 35 rhesus macaques euthanized for ICD during a 7-month period and described demographic, clinical, histologic, and immunologic commonalities. We found a trend of historic Campylobacter spp. and trichomonad infections. Furthermore, rhesus macaques with ICD demonstrated loss of normal colonic adherent bacterium, identified in this study as Helicobacter macacae; increased abundance of Pentatrichomonas hominis; and increased frequency of colonic serotonin-positive enterochromaffin cells. Interestingly, colonic and ileal T-helper cells of animals with ICD manifested decreased capacity for expression of certain cytokines, in particular interleukin (IL)–4 and IL-13. These data further describe a common ailment and suggest new avenues to identify complex interactions involved in the etiology of recurring diarrhea in young rhesus macaques.